Answer:
c = -9
Explanation:
- 4c + 25 + c = 3c + 79 Combine like terms.
- 4c + c + 25 = 3c + 79
- 3c + 25 = 3c + 79
- 3c + 3c + 25 = 3c + 3c + 79
25 = 6c + 79
25 - 79 = 6c + 79 - 79
- 54 = 6c
-54/6 = 6c/6
-54/6 = c
-9 = c
There aren't 2 answers, you could have 2 answers if one of the c's was squared. Here is another way to do the math.
- 4c + 25 + c = 3c + 79
- 4c + c + 25 = 3c + 79
- 3c + 25 = 3c + 79
- 3c - 3c + 25 = 3c - 3c + 79
- 6c + 25 = 79
- 6c + 25 - 25 = 79 - 25
- 6c = 54
- 6c/- 6 = 54/- 6
c = 54/- 6
c = - 9